PERBANDINGAN KUALITAS LAYANAN BANK SYARIAH DAN BANK KONVENSIONAL (Pendekatan Model PBZ) - H. Abdul Choliq; Irwan Misbach (Jurnal Keuangan dan Perbankan, 2016)
AbstractThe purpose of this study was to determine differences in the customers perception of the service quality ofIslamic banks and conventional bank. This is done because the Islamic bank (sharia) is a bank that is operationallydifferent from conventional banks although in some instances. They have similarities, especially in thetechnical side. This study measured differences in the services quality provided by Islamic banks and conventionalbanks in Makassar. The number of respondents are 200 people with accidental sampling method.Testing the hypothesis in this study used a comparative test of independent t-test (independent samples). Theresults of this study were no significant difference between the service quality Islamic banks with conventionalbanks. The study also only measures customer perceptions about the service quality of the bank are perceivedand not to measure their perceptions of the service quality of expected, so it cannot be proven levels of customersatisfaction.